Preparation method of a BiVO4 / FeCoNiOOH-based photocatalytic water decomposition catalyst

CN122918631APending Publication Date: 2026-10-16NANCHANG HANGKONG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611293881.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

目前业内尚无成熟的BiVO4与FeCoNiOOH复合制备工艺,缺乏界面调控与结构优化方案,无法充分发挥两种材料的协同优势

Benefits of technology

[0015] 1. The BiVO4/FeCoNiOOH catalyst prepared in this invention can efficiently catalyze water splitting under photoelectric effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122918631A_ABST
    Figure CN122918631A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a BiVO4 / FeCoNiOOH-based photocatalytic water decomposition catalyst, and the preparation method comprises the following steps: firstly, preparing BiVO4; and then, further converting the BiVO4 into BiVO4 / FeCoNiOOH on the basis of the BiVO4, so as to obtain the BiVO4 / FeCoNiOOH-based photocatalytic water decomposition catalyst. The BiVO4 / FeCoNiOOH catalyst prepared by the method can efficiently catalyze water decomposition under the action of photoelectricity, and the preparation method is simple, low in cost and suitable for large-area popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photoelectrocatalytic water splitting technology, and in particular to a method for preparing a photoelectrocatalytic water splitting catalyst based on BiVO4 / FeCoNiOOH. Background Technology

[0002] With global energy shortages, the development of clean and renewable energy has become a key research focus in the energy sector. Hydrogen energy, as a zero-pollution, high-calorific-value green energy source, is an ideal alternative to fossil fuels. Photoelectrochemical water splitting technology can utilize solar energy to produce hydrogen, with mild reaction conditions and strong sustainability. It is a key technology for the large-scale production of green hydrogen and has extremely high scientific research and application value. The core of photoelectrochemical water splitting is the photoelectrode material, which directly determines the system's photoelectric conversion efficiency and catalytic performance. Among many n-type semiconductor materials, monoclinic BiVO4 has a band gap of approximately 2.4 eV, exhibiting excellent visible light response performance. It also possesses advantages such as being non-toxic, low-cost, and having good electrochemical stability, making it the mainstream material in the field of water oxidation photoelectrocatalysis, with a high theoretical energy conversion efficiency.

[0003] However, pure-phase BiVO4 exhibits significant performance defects that severely restrict its industrial application. It suffers from low photogenerated electron-hole pair separation efficiency, severe bulk recombination, slow charge migration rate, high interfacial transport resistance, and low photon utilization. Furthermore, the water oxidation reaction kinetics are slow, the pure-phase BiVO4 surface lacks catalytically active sites, has a high reaction overpotential, and numerous intrinsic defects, further exacerbating carrier recombination and resulting in actual photocurrent density and catalytic stability far below theoretical levels.

[0004] Existing technologies often modify BiVO4 by loading transition metal hydroxyl oxides. Traditional single-metal and bimetallic hydroxyl oxides (NiOOH, NiFeOOH, etc.) can slightly improve catalytic performance, but they suffer from problems such as single active sites, weak metal synergistic effects, and insufficient charge control capabilities, reaching a bottleneck in performance improvement. Ternary FeCoNiOOH hydroxyl oxides possess synergistic effects from multiple active sites, tunable electronic structure, and excellent conductivity, effectively reducing water oxidation overpotential, accelerating charge transfer, and suppressing carrier recombination. Currently, there is no mature process for preparing BiVO4 and FeCoNiOOH composites, and there is a lack of interface control and structural optimization schemes, which prevents the full utilization of the synergistic advantages of the two materials.

[0005] Based on the above technical background, this invention develops a method for preparing a photoelectrocatalytic water splitting catalyst based on BiVO4 / FeCoNiOOH, which has not been reported before. Summary of the Invention

[0006] The purpose of this invention is to solve the technical problems existing in the prior art and to provide a method for preparing a photoelectrocatalytic water splitting catalyst based on BiVO4 / FeCoNiOOH.

[0007] To achieve the above objectives, the present invention provides a method for preparing a BiVO4 / FeCoNiOOH-based photoelectrocatalytic water splitting catalyst, characterized in that: the preparation method first prepares a BiVO4 photoanode, and then further converts the BiVO4 into a BiVO4 / FeCoNiOOH photoanode, thereby obtaining a BiVO4 / FeCoNiOOH-based photoelectrocatalytic water splitting catalyst. Specifically, it includes the following steps:

[0008] Step (1): Preparation of BiVO4 photoanode

[0009] Dissolve 3.32 g of potassium iodide (KI) in 50 mL of deionized water, then add 0.970 g of bismuth nitrate pentahydrate (Bi(NO3)3∙5H2O) and adjust the pH to a constant value. Dissolve 0.49 g of p-benzoquinone in 20 mL of anhydrous ethanol, stir well, and then add it dropwise to the above solution using a dropper. The resulting solution is named Solution A. Conductive glass (FTO, active area 1.0 × 1.0 cm²) is used. 2 Using a platinum sheet electrode as the working electrode, a saturated Ag / AgCl electrode as the counter electrode, and solution A as the electrolyte, electrodeposition was performed at a certain voltage for a certain time. The FTO was removed, rinsed with deionized water and anhydrous ethanol, and dried at 25°C for 1 h. A certain amount of vanadium acetylacetonate (VO(acac)2) was dissolved in 1 mL of dimethyl sulfoxide, and 60 μL was added dropwise to the FTO. After drying, the FTO was placed in a muffle furnace and heated to a certain temperature at a rate of 2°C / min and held for 2 h. After cooling to room temperature, the FTO was then subjected to electrodeposition at 1.0 mol / L... -1 The material obtained by soaking in NaOH solution for 1 h was named BiVO4 photoanode.

[0010] Step (2): Preparation of BiVO4 / FeCoNiOOH photoanode

[0011] 0.52 g of nickel nitrate hexahydrate (Ni(NO3)2∙6H2O), 0.83 g of ferrous sulfate heptahydrate (FeSO4∙7H2O), and 0.34 g of cobalt nitrate hexahydrate (Co(NO3)2∙7H2O) were dissolved in 100 mL of deionized water, and the resulting solution was named solution B. Using a BiVO4 photoanode as the working electrode, a platinum sheet electrode as the counter electrode, and Ag / AgCl as the reference electrode, and solution B as the electrolyte, photoelectrodeposition was performed for a certain period of time under a 300 W xenon lamp illumination and an applied voltage.

[0012] Preferably, the pH value adjusted in step (1) is in the range of 1-3, the voltage applied during electrodeposition is in the range of 0.05-0.2 V vs. Ag / AgCl, the electrodeposition time is in the range of 200-500 s, the amount of vanadium acetylacetonate (VO(acac)2) taken is in the range of 0.053-0.212 g, and the temperature reached by the muffle furnace is in the range of 400-600℃.

[0013] Preferably, the voltage applied in step (2) for photoelectrodeposition is in the range of 0.25-1 V vs. Ag / AgCl, and the deposition time is in the range of 60-100 min.

[0014] Beneficial effects of this invention:

[0015] 1. The BiVO4 / FeCoNiOOH catalyst prepared in this invention can efficiently catalyze water splitting under photoelectric effect.

[0016] 2. The BiVO4 / FeCoNiOOH catalyst prepared by this invention is simple to prepare, low in cost, and suitable for large-scale application. Attached Figure Description

[0017] The accompanying drawings, which are provided to further illustrate the invention and constitute a part of this invention, are illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention.

[0018] Figure 1 This is a scanning electron microscope image of the BiVO4 / FeCoNiOOH catalyst prepared in Specific Example 2 of the present invention;

[0019] Figure 2 The graph shows the performance of the BiVO4 / FeCoNiOOH catalyst prepared in Specific Example 2 of this invention in catalyzing water splitting under photoelectric effect. Detailed Implementation

[0020] This section will describe in detail specific embodiments of the present invention. Preferred embodiments of the present invention are shown in the accompanying drawings. The purpose of the drawings is to supplement the textual description with graphics, so that people can intuitively and vividly understand each technical feature and overall technical solution of the present invention, but they should not be construed as limiting the scope of protection of the present invention. Specific Implementation Example 1

[0022] Step (1): Preparation of BiVO4 photoanode

[0023] Dissolve 3.32 g of potassium iodide (KI) in 50 mL of deionized water, then add 0.970 g of bismuth nitrate pentahydrate (Bi(NO3)3∙5H2O) and adjust the pH to 1. Dissolve 0.49 g of p-benzoquinone in 20 mL of anhydrous ethanol, stir well, and then add it dropwise to the above solution using a dropper. The resulting solution is named Solution A. Conductive glass (FTO, active area 1.0 × 1.0 cm²) is used. 2 Using a platinum sheet electrode as the working electrode, a saturated Ag / AgCl electrode as the counter electrode, and solution A as the electrolyte, electrodeposition was performed for 200 s at 0.05 V vs. Ag / AgCl. The FTO was removed, rinsed with deionized water and anhydrous ethanol, and dried at 25 °C for 1 h. 0.053 g of vanadium acetylacetonate (VO(acac)2) was dissolved in 1 mL of dimethyl sulfoxide, and 60 μL was added dropwise to the FTO. After drying, the FTO was placed in a muffle furnace and heated to 400 °C at a rate of 2 °C / min and held for 2 h. After cooling to room temperature, the FTO was then subjected to a 1.0 mol L⁻¹... -1 The material obtained by soaking in NaOH solution for 1 h was named BiVO4 photoanode.

[0024] Step (2): Preparation of BiVO4 / FeCoNiOOH photoanode

[0025] 0.52 g of nickel nitrate hexahydrate (Ni(NO3)2∙6H2O), 0.83 g of ferrous sulfate heptahydrate (FeSO4∙7H2O), and 0.34 g of cobalt nitrate hexahydrate (Co(NO3)2∙7H2O) were dissolved in 100 mL of deionized water, and the resulting solution was named solution B. Using a BiVO4 photoanode as the working electrode, a platinum sheet electrode as the counter electrode, and Ag / AgCl as the reference electrode, solution B was used as the electrolyte. Irradiation was provided by a 300 W xenon lamp, and photoelectrodeposition was performed for 60 min with an applied voltage of 0.2 V vs. Ag / AgCl. Specific Implementation Example 2

[0027] Step (1): Preparation of BiVO4 photoanode

[0028] Dissolve 3.32 g of potassium iodide (KI) in 50 mL of deionized water, then add 0.970 g of bismuth nitrate pentahydrate (Bi(NO3)3∙5H2O) to adjust the pH to 1.7. Dissolve 0.49 g of p-benzoquinone in 20 mL of anhydrous ethanol, stir well, and then add it dropwise to the above solution using a dropper. The resulting solution is named Solution A. Conductive glass (FTO, active area 1.0 × 1.0 cm²) is used. 2Using a platinum sheet electrode as the working electrode, a saturated Ag / AgCl electrode as the counter electrode, and solution A as the electrolyte, electrodeposition was performed for 300 s at 0.1 V vs. Ag / AgCl. The FTO was removed, rinsed with deionized water and anhydrous ethanol, and dried at 25 °C for 1 h. 0.053 g of vanadium acetylacetonate (VO(acac)2) was dissolved in 1 mL of dimethyl sulfoxide, and 60 μL was added dropwise to the FTO. After drying, the FTO was placed in a muffle furnace and heated to 450 °C at a rate of 2 °C / min and held for 2 h. After cooling to room temperature, the FTO was then subjected to a 1.0 mol L⁻¹... -1 The material obtained by soaking in NaOH solution for 1 h was named BiVO4 photoanode.

[0029] Step (2): Preparation of BiVO4 / FeCoNiOOH photoanode

[0030] 0.52 g of nickel nitrate hexahydrate (Ni(NO3)2∙6H2O), 0.83 g of ferrous sulfate heptahydrate (FeSO4∙7H2O), and 0.34 g of cobalt nitrate hexahydrate (Co(NO3)2∙7H2O) were dissolved in 100 mL of deionized water, and the resulting solution was named solution B. Using a BiVO4 photoanode as the working electrode, a platinum sheet electrode as the counter electrode, and Ag / AgCl as the reference electrode, solution B was used as the electrolyte. Irradiation was provided by a 300 W xenon lamp, and photoelectrodeposition was performed for 80 min with an applied voltage of 0.25 V vs. Ag / AgCl. Specific Implementation Example 3

[0032] Step (1): Preparation of BiVO4 photoanode

[0033] Dissolve 3.32 g of potassium iodide (KI) in 50 mL of deionized water, then add 0.970 g of bismuth nitrate pentahydrate (Bi(NO3)3∙5H2O) to adjust the pH to 2.5. Dissolve 0.49 g of p-benzoquinone in 20 mL of anhydrous ethanol, stir well, and then add it dropwise to the above solution using a dropper. The resulting solution is named Solution A. Conductive glass (FTO, active area 1.0 × 1.0 cm²) is used. 2Using a platinum sheet electrode as the working electrode, a saturated Ag / AgCl electrode as the counter electrode, and solution A as the electrolyte, electrodeposition was performed at 0.15 V vs. Ag / AgCl for 300 s. The FTO was removed, rinsed with deionized water and anhydrous ethanol, and dried at 25 °C for 1 h. 0.159 g of vanadium acetylacetonate (VO(acac)2) was dissolved in 1 mL of dimethyl sulfoxide, and 60 μL was added dropwise to the FTO. After drying, the FTO was placed in a muffle furnace and heated to 500 °C at a rate of 2 °C / min and held for 2 h. After cooling to room temperature, the FTO was then subjected to a 1.0 mol L⁻¹... -1 The material obtained by soaking in NaOH solution for 1 h was named BiVO4 photoanode.

[0034] Step (2): Preparation of BiVO4 / FeCoNiOOH photoanode

[0035] 0.52 g of nickel nitrate hexahydrate (Ni(NO3)2∙6H2O), 0.83 g of ferrous sulfate heptahydrate (FeSO4∙7H2O), and 0.34 g of cobalt nitrate hexahydrate (Co(NO3)2∙7H2O) were dissolved in 100 mL of deionized water, and the resulting solution was named solution B. Using a BiVO4 photoanode as the working electrode, a platinum sheet electrode as the counter electrode, and Ag / AgCl as the reference electrode, solution B was used as the electrolyte. Irradiation was provided by a 300 W xenon lamp, and photoelectrodeposition was performed for 80 min with an applied voltage of 0.75 V vs. Ag / AgCl.

[0036] Specific Experiment Example 4

[0037] Step (1): Preparation of BiVO4 photoanode

[0038] Dissolve 3.32 g of potassium iodide (KI) in 50 mL of deionized water, then add 0.970 g of bismuth nitrate pentahydrate (Bi(NO3)3∙5H2O) to adjust the pH to 3. Dissolve 0.49 g of p-benzoquinone in 20 mL of anhydrous ethanol, stir well, and then add it dropwise to the above solution using a dropper. The resulting solution is named Solution A. Conductive glass (FTO, active area 1.0 × 1.0 cm²) is used. 2Using a platinum sheet electrode as the working electrode, a saturated Ag / AgCl electrode as the counter electrode, and solution A as the electrolyte, electrodeposition was performed at 0.2 V vs. Ag / AgCl for 500 s. The FTO was removed, rinsed with deionized water and anhydrous ethanol, and dried at 25 °C for 1 h. 0.212 g of vanadium acetylacetonate (VO(acac)2) was dissolved in 1 mL of dimethyl sulfoxide, and 60 μL was added dropwise to the FTO. After drying, the FTO was placed in a muffle furnace and heated to 600 °C at a rate of 2 °C / min and held for 2 h. After cooling to room temperature, the FTO was then subjected to a 1.0 mol L⁻¹... -1 The material obtained by soaking in NaOH solution for 1 h was named BiVO4 photoanode.

[0039] Step (2): Preparation of BiVO4 / FeCoNiOOH photoanode

[0040] 0.52 g of nickel nitrate hexahydrate (Ni(NO3)2∙6H2O), 0.83 g of ferrous sulfate heptahydrate (FeSO4∙7H2O), and 0.34 g of cobalt nitrate hexahydrate (Co(NO3)2∙7H2O) were dissolved in 100 mL of deionized water, and the resulting solution was named solution B. Using a BiVO4 photoanode as the working electrode, a platinum sheet electrode as the counter electrode, and Ag / AgCl as the reference electrode, solution B was used as the electrolyte. Irradiation was provided by a 300 W xenon lamp, and photoelectrodeposition was performed for 100 min with an applied voltage of 1 V vs. Ag / AgCl.

[0041] The BiVO4 / FeCoNiOOH catalyst prepared by this invention can efficiently catalyze water splitting under photoelectric action, and its preparation is simple, low-cost, and suitable for large-scale application.

[0042] Without causing conflict, those skilled in the art can freely combine and use the above-mentioned additional technical features.

[0043] The above description is only a preferred embodiment of the present invention. Any technical solution that achieves the purpose of the present invention by essentially the same means is within the protection scope of the present invention.

Claims

1. A method for preparing a photoelectrochemical water splitting catalyst based on BiVO4 / FeCoNiOOH, characterized in that: The preparation method first prepares a BiVO4 photoanode, and then further converts the BiVO4 into a BiVO4 / FeCoNiOOH photoanode, thereby obtaining a BiVO4 / FeCoNiOOH-based photoelectrochemical water splitting catalyst. Specifically, it includes the following steps: Step (1): Preparation of BiVO4 photoanode Dissolve 3.32 g of potassium iodide (KI) in 50 mL of deionized water, then add 0.970 g of bismuth nitrate pentahydrate (Bi(NO3)3∙5H2O) and adjust the pH to a constant value. Dissolve 0.49 g of p-benzoquinone in 20 mL of anhydrous ethanol, stir well, and then add it dropwise to the above solution using a dropper. The resulting solution is named Solution A. Conductive glass (FTO, active area 1.0 × 1.0 cm²) is used. 2 Using a platinum sheet electrode as the working electrode, a saturated Ag / AgCl electrode as the counter electrode, and solution A as the electrolyte, electrodeposition was performed at a certain voltage for a certain time. The FTO was removed, rinsed with deionized water and anhydrous ethanol, and dried at 25°C for 1 h. A certain amount of vanadium acetylacetonate (VO(acac)2) was dissolved in 1 mL of dimethyl sulfoxide, and 60 μL was added dropwise to the FTO. After drying, the FTO was placed in a muffle furnace and heated to a certain temperature at a rate of 2°C / min and held for 2 h. After cooling to room temperature, the FTO was then subjected to electrodeposition at 1.0 mol / L... -1 The material obtained by soaking in NaOH solution for 1 h was named BiVO4 photoanode. Step (2): Preparation of BiVO4 / FeCoNiOOH photoanode 0.52 g of nickel nitrate hexahydrate (Ni(NO3)2∙6H2O), 0.83 g of ferrous sulfate heptahydrate (FeSO4∙7H2O), and 0.34 g of cobalt nitrate hexahydrate (Co(NO3)2∙7H2O) were dissolved in 100 mL of deionized water, and the resulting solution was named solution B. Using a BiVO4 photoanode as the working electrode, a platinum sheet electrode as the counter electrode, and Ag / AgCl as the reference electrode, solution B was used as the electrolyte. The solution was irradiated by a 300 W xenon lamp, and a certain voltage was applied for photoelectrode deposition for a specified time.

2. The method for preparing a photoelectrocatalytic water splitting catalyst based on BiVO4 / FeCoNiOOH according to claim 1, characterized in that: In step (1), the pH value is adjusted to a range of 1-3, the voltage applied during electrodeposition is 0.05-0.2 V vs. Ag / AgCl, the electrodeposition time is 200-500 s, the amount of vanadium acetylacetone oxide (VO(acac)2) taken is 0.053-0.212 g, and the temperature reached by the muffle furnace is 400-600℃.

3. The method for preparing a photoelectrocatalytic water splitting catalyst based on BiVO4 / FeCoNiOOH according to claim 1, characterized in that: In step (2), the voltage applied for photoelectrodeposition ranges from 0.25 to 1 V vs. Ag / AgCl, and the deposition time ranges from 60 to 100 min.